THE EFFECT OF CROSSWORD PUZZLE LEARNING MEDIA ON STUDENTS' SCIENCE LEARNING OUTCOMES IN FIFTH-GRADE SDN 28 SINGKAWANG - Angreini, Anggie; Marhayani, Dina Anika; Utama, Erdi Guna (PROGRES PENDIDIKAN, 2025)
The purpose of this study was to describe whether there is a difference in learning outcomes between students who are taught using crossword puzzle media and those who do not use crossword puzzle media in the science subject of grade V students of SDN 28 Singkawang and to describe how much influence the crossword puzzle learning media has on students' learning outcomes in the science subject of grade V SDN 28 Singkawang . The data in this study are the learning outcomes of the control class and the learning outcomes of the experimental class. The data source is grade V students of SDN 28 Singkawang. The sampling technique used in this study is non-probability . The data collection technique used is an essay test technique . Based on the results of the study, 26 students from class A were obtained as the control class and 26 students from class B as the experimental class. The control class obtained the highest score in the pre-test, which was 90, and the post -test class was 95. The lowest score in the pre-test was 43 and the post-test was 43. The experimental class obtained the highest score in the pre-test, which was 90, and the post-test was 95. The lowest score in the pre-test was 43 and the post-test was 60. The results of this study can be assumed in the 2013 curriculum in learning Natural Sciences.